Cohesión y Adaptabilidad de la Funcionalidad Familiar en Embarazos Adolescentes entre los 13 y 19años. (2022)
The objective of this research is to determine family functionality in a group of pregnant adolescents between 13 and 19 years of age, residents of Tomarrazón, Municipality of Riohacha. For its development, the dimensions of cohesion and adaptability are identified based on Olson's circumplex model. This research is carried out under a quantitative, nonexperimental, cross-sectional design, with a descriptive scope. The population that is part of this research project are pregnant adolescents between 13 and 19 years of age, with a total sample of 20 adolescents.